2020
DOI: 10.1021/acs.jpcc.0c04678
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Atomic-Level Correlation between Geometric and Electronic Structure at a Metal–Organic Interface

Abstract: The interface of π-conjugated organic molecules with metal surfaces plays a crucial role in determining the efficiency of organic-based electronic devices. Because the interface is buried under the molecule, it is often experimentally inaccessible. Here, we propose a way of simultaneous structural and electronic characterization of the interface of the metal−organic system. Using the molecular manipulation technique of scanning tunneling microscope, we conducted a systematic study of geometric and electronic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
3
2
0
Order By: Relevance
“…Recently, STS results [45] indicated that the LUMO CuPc on Au(110), in a very lowcoverage regime (≤0.3 SL), is always located above EF for the Au surface, in agreement with our assignment at 0.3 SL and confirming the weak interaction, even for coverages below the molecular chain formation and a negligible substrate/molecule CT.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Recently, STS results [45] indicated that the LUMO CuPc on Au(110), in a very lowcoverage regime (≤0.3 SL), is always located above EF for the Au surface, in agreement with our assignment at 0.3 SL and confirming the weak interaction, even for coverages below the molecular chain formation and a negligible substrate/molecule CT.…”
Section: Resultssupporting
confidence: 91%
“…Recently, STS results [45] indicated that the LUMO CuPc on Au(110), in a very lowcoverage regime (≤0.3 SL), is always located above E F for the Au surface, in agreement with our assignment at 0.3 SL and confirming the weak interaction, even for coverages below the molecular chain formation and a negligible substrate/molecule CT. The IPES data of the CuPc/Au(110) system (Figure 3b) show that the emission close to EF is dominated by the metallic substrate, while the molecular state intensities become prominent at about 0.5-0.7 SL, corresponding to the (5 × 5)-symmetry reconstruction of the interface [12].…”
Section: Resultssupporting
confidence: 90%
“…We schematically illustrate the adsorption structure for A-CuPc in Figure 2(g), where the trough is locally filled with four Au adatoms, onto which the molecule adsorbs. Note that the number of Au adatoms was typically four but distributed between two to six, as we reported previously [25]. Figure 2(f ) shows the atomic-resolution STM image of the "dark" area.…”
Section: Resultssupporting
confidence: 64%
“…The results presented here indicate that surface reconstruction occurs from the initial CuPc adsorption stage. We assume that such a surface reconstruction is inherent in the system of π-conjugated planar molecules (e.g., CuPc) on "corrugated" surfaces [e.g., Au(110)-(1 × 2)]; the molecule binds to the surface via the electronic coupling between the organic ligand (isoindole rings) and substrate [7,25,29]. Therefore, the molecule maximizes the contact area, i.e., the overlap between the molecular orbitals and surface electronic states.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation